Diversidade, etnobotânica e propagação de cabeça-de-frade (Melocactus Link & Otto - Cactaceae) no estado de Sergipe - Bravo Filho, Eronides Soares (2014)
The Cactaceae family is botanically distributed in 100 genera and about 1500 species, it is subdivided into four Subfamilies that are: Maihuenoideae, Pereskeoideae, Opuntioideae and Cactoideae. This family includes the botanical group heliophila plants, dicotyledonous angiosperm, it represents the second most numerous group of Neotropical region and they are found in a great diversity of climate, soil and ecosystems, with higher occurrence of Caatinga, tropical forests, Cerrado, rock fields and Sandbanks. The cacti of the genus Melocactus (Link & Otto) are part of the subfamily Cactoideae and comprises a total of 38 species and 25 subspecies. Perennial plant with non-segmented stem has a unique feature of the group that is the presence of the terminal cephalium and the exclusive propagation by seed. Despite numerous scientific studies on cacti in Brazil, the geographical distribution, population size and conservation status of most species has been little studied, worrying fact since the totality of currently cataloged Melocactus nine are listed with endangered. Therefore, this study aimed to map and survey Melocactus species that occur in the State of Sergipe, research the ethnobotanical interactions of the Cactaceae in the state and promote seed germination with the substrates test of M. violaceus and zehntneri. The instruments used were research fields in which were determined the geographical coordinates, altitude, presence of species in the reproductive phase and fruiting. The ethnobotanical data were obtained through semi-structured research with the application of a standardized questionnaire to 36 residents. For the germination experiment experimental design was completely randomized with four replications of 25 seeds. The Relative Frequency of germination, mean germination time, speed of germination index, shoot length, length and diameter length Radicle were evaluated. Through this work was recorded the occurrence of a new species of Melocactus and as well as the occurrence of this genus in 18 counties in the state of Sergipe. In relation to the ethnobotanical survey species of cacti were identified, they were grouped into four categories of uses: medical, food and feed, construction and manufacture of objects, ornamental and mysticism. Regarding the germination experiment, M. violaceus species showed higher germination rate than the species M. zehntneri, the soaked / dehydrated and not soaked seeds showed no significant difference in germination and the substrate that showed the best results for M. and M. violaceus was zehntneri S2(50% + 50% washed sand topsoil) and S1(100% sand washed) respectively.